2020
DOI: 10.1038/s41467-020-16090-2
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic account of serotonin’s impact on mood

Abstract: Selective serotonin reuptake inhibitors (SSRIs) constitute a first-line antidepressant intervention, though the precise cognitive and computational mechanisms that explain treatment response remain elusive. Using week-long SSRI treatment in healthy volunteer participants, we show serotonin enhances the impact of experimentally induced positive affect on learning of novel, and reconsolidation of previously learned, reward associations. Computational modelling indicated these effects are best accounted for by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 54 publications
7
48
0
Order By: Relevance
“…These findings suggest that SSRI transiently accelerate hedonic recovery from stress, but more importantly lead to stable cognitive/behavioral response to ambiguous cue ( Alboni et al, 2017 ). This is consistent with growing clinical data suggesting that SSRI induce a more “rosy perception” ( Michely et al, 2020 ) and provide a novel experimental paradigm to study this phenomenon in mice.…”
Section: Operant Wall Systemssupporting
confidence: 90%
“…These findings suggest that SSRI transiently accelerate hedonic recovery from stress, but more importantly lead to stable cognitive/behavioral response to ambiguous cue ( Alboni et al, 2017 ). This is consistent with growing clinical data suggesting that SSRI induce a more “rosy perception” ( Michely et al, 2020 ) and provide a novel experimental paradigm to study this phenomenon in mice.…”
Section: Operant Wall Systemssupporting
confidence: 90%
“…Another interesting direction is to investigate whether the proposed positive-feedback loop (borne of heightened internal cogitation driven by memory modification paired with weaker learning from external contingencies) relates to the observation that dynamical signatures of positive-feedback loops precede depressive states (e.g., Leemput et al, 2014). Finally, it is important to note that the positive-feedback loop we are proposing is in the opposite direction as one recently postulated to lead to virtuous cycles of reward surprise and escalating mood caused by serotonergic agonists (Michely, Eldar, Martin, & Dolan, 2020), yet at extremes create oscillatory mood dynamics that could contribute to the symptoms of Bipolar Disorders (Eldar & Niv, 2015).…”
Section: Model Parametersmentioning
confidence: 64%
“…SSRI treatments and successful interoceptive therapies in depression and anxiety (Khoury et al, 2018) may be found to overlap in mechanism as they ameliorate blunted affect (Paulus et al, 2019) or break maladaptive cognitive cycles (Roy-Byrne et al, 2006). Perceptual biases that appear before clinical effects of SSRIs are observed and are thought to predict clinical outcomes (Harmer & Cowen, 2013;Michely et al, 2020) may be discovered to have interoceptive foundations. Anxiogenic effects arising near the onset of SSRI treatment (Taylor et al, 2006) may be due interoceptive inputs suddenly being processed in a new way.…”
Section: Implications For Other Cognitionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors (SSRIs) change the synaptic availability of serotonin. In addition to their clinical effects, even single doses affect cognition, including learning (Chamberlain et al, 2006;Michely et al, 2020;Scholl et al, 2017), social perception (Harmer & Cowen, 2013), and choice (Crockett et al, 2010). They also alter central nervous system plasticity (Castrén & Rantamäki, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation